Ada Apa Dengan Indonesia Cinema? (What’s up with Indonesian Cinema?) Interviews with Filmmakers Riri Riza and Rudy Soedjarwo - Ciecko, Anne (Asian Cinema, 2006)
With the continued visibility and impact of Thai cinema at festivals worldwide, curious programmers are turning their gaze to other Southeast Asian countries. The new energy of contemporary Indonesian filmmaking was recognized with a total of eight shorts and features at the 10th annual Pusan International Film Festival and eleven films at the 35th International Film Festival Rotterdam… Below are interviews with two more of Indonesia’s most critically acclaimed and commercially successful feature film directors of this generation, Riri Riza and Rudy Soedjarwo.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9hYy4xNy4xLjkwXzE